2018
DOI: 10.3390/v10110598
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Zika Virus Infection during Pregnancy

Abstract: Zika virus (ZIKV) emerged suddenly in the Americas in 2015 and was associated with a widespread outbreak of microcephaly and other severe congenital abnormalities in infants born to mothers infected during pregnancy. Vertical transmission of ZIKV in humans was confirmed when viral RNA was detected in fetal and placental tissues, and this outcome has been recapitulated experimentally in animals. Unlike other flaviviruses, ZIKV is both arthropod- and sexually-transmitted, and has a broad tissue tropism in humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 94 publications
2
44
0
1
Order By: Relevance
“…Several lines of evidence showed the existence of ZIKV antigens in the chronic villi of a human placenta from a mother who gave birth to an infant with microcephaly , and isolation of ZIKV RNA from placental tissue of mice infected with the ZIKV (Caine et al, 2018), suggesting that the ZIKV may penetrate the placental barrier to infect the infant brain. Recent studies reported that the ZIKV is able to infect and replicate in Hofbauer cells that are primary human placental macrophages and in cytotrophoblasts, suggesting a route of intrauterine transmission that the ZIKV crosses the fetal compartment by directly infecting the placental cells (Quicke et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence showed the existence of ZIKV antigens in the chronic villi of a human placenta from a mother who gave birth to an infant with microcephaly , and isolation of ZIKV RNA from placental tissue of mice infected with the ZIKV (Caine et al, 2018), suggesting that the ZIKV may penetrate the placental barrier to infect the infant brain. Recent studies reported that the ZIKV is able to infect and replicate in Hofbauer cells that are primary human placental macrophages and in cytotrophoblasts, suggesting a route of intrauterine transmission that the ZIKV crosses the fetal compartment by directly infecting the placental cells (Quicke et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Passive immunization reduces or prevents ZIKV infection in nonpregnant rodents and macaques (23,25,26,31,32). In addition, antibodies diminish ZIKV viral burden in the placenta and fetal organs, and also reduce fetal demise in mouse pregnancy models (33)(34)(35). Some of these ZIKV mouse pregnancy models reproduce features of the human disease, including brain pathology (4-6).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mouse models have been proposed to decipher the mechanisms of ZIKV disease pathogenesis (14, 15). These models allow the investigation of several key features of human infection, such as neuronal damage (16, 17), sexual and vertical transmission (1821), fetal demise and CZS (2225). However, while non-structural ZIKV proteins efficiently inhibit innate antiviral responses in humans (26, 27) allowing viral replication, ZIKV replicates poorly in wild-type mice due to its NS5 protein’s inability to antagonize STAT2 and type I interferon (IFN) response as in humans (28).…”
mentioning
confidence: 99%